Social Impact of Early Marriage on Reproductive Health - Werdyaningsih, Endang; Iqbal Ahmad, Muhammad; Serli, Serli; Meiliani Yulis, Dian; Citra, Auliya; Supriatin, Supriatin; Andi Latif, Sarifudin (International Journal of Health Sciences, 2023)
Early marriage is a marriage that occurs in a woman with an age status below 20 years where the state of her reproductive organs is not fully mature and is still in the growth stage. This period is referred to as the young reproductive period, which means that although it can become pregnant and give birth, the body is not ready to become pregnant. Meanwhile, reproductive health is a complete physical, mental and social condition, not just free from disease or disability in all aspects related to the reproductive system. The purpose of this study was to determine the level of Knowledge of Midwifery Students of Stikes Amanah Makassar Level II about the Impact of Early Marriage on Reproductive Health. This type of research is descriptive research and survey research design with direct interviews using questionnaires. The population in this study were all level II students who existed and studied at D3 Midwifery Stikes Amanah Makassar and the sample of this study were all level II students who existed and studied at D3 Midwifery Stikes Amanah Makassar and at the time the research was conducted, namely 25 people. The sampling technique used in this study was exedent sampling.